Orthogonal, modular anion–cation and cation–anion self-assembly using pre-programmed anion binding sites. Issue 10 (14th February 2023) - Dhara, Ayan; Fadler, Rachel E.; Chen, Yusheng; Köttner, Laura A.; Van Craen, David; Carta, Veronica; Flood, Amar H.
Abstract : Use of pre-programmed anion binding sites provide structure-directing elements in subcomponent self-assembly that operate in an orthogonal way to the traditional role of cations. Abstract : Subcomponent self-assembly relies on cation coordination whereas the roles of anions often only emerge during the assembly process. When sites for anions are instead pre-programmed, they have the potential to be used as orthogonal elements to build up structure in a predictable and modular way. We explore this idea by combining cation (M + ) and anion (X − ) binding sites together and show the orthogonal and modular build up of structure in a multi-ion assembly. Cation binding is based on a ligand (L) made by subcomponent metal-imine chemistry (M + = Cu +, Au + ) while the site for anion binding (X − = BF4 −, ClO4 − ) derives from the inner cavity of cyanostar (CS ) macrocycles. The two sites are connected by imine condensation between a pyridyl-aldehyde and an aniline-modified cyanostar. The target assembly [L M-CS -X-CS -ML ], + generates two terminal metal complexation sites (L M and ML ) with one central anion-bridging site (X) defined by cyanostar dimerization. We showcase modular assembly by isolating intermediates when the primary structure-directing ions are paired with weakly coordinating counter ions. Cation-directed (Cu + ) or anion-bridged (BF4 − ) intermediates can be isolated along either cation–anion or anion–cation pathways. Different products can also be prepared in a modular way using Au + and ClO4 − . This is also the first use of gold(i ) in subcomponent self-assembly. Pre-programmed cation and anion binding sites combine with judicious selection of spectator ions to provide modular noncovalent syntheses of multi-component architectures.